PENGARUH PENGHARGAAN, HUKUMAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi kasus UD. Langgan Wajar Karaban) - Euis Widiati; Alda Riza Merdekawati (Jurnal Akuntansi Dan Manajemen, 2022)
This study aims to determine the effect of reward, punishment, and work discipline on employee performance at UD. Subscribe to Fair News. In this study, the independent variables consist of reward, punishment, and work discipline. The dependent variable is employee performance. This research is quantitative research where the respondents in this study are all employees at UD. Subscribe to Fair Karaban as many as 86 respondents. The analysis used in this research is a validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis testing. The results of this study indicate that reward, punishment, and work discipline have a significant effect on employee performance.